The Impact of Sexual Violence Victimization on Acculturative Stress and Hazardous Drinking Among North Korean Refugee Women in South Korea - Choi, Jaeyong (Violence against women, 2025)
North Korean refugee women face significant risks of traumatic experiences, including sexual exploitation and violence, both in North Korea and during migration. However, there is limited research on the long-term effects of sexual violence among these women. Using data from 245 North Korean refugee women, collected by the National Human Rights Commission of Korea in 2017, we examined the impact of sexual violence victimization during pre-migration and intermediate stages on acculturative stress and hazardous drinking. Our findings revealed that women who experienced sexual violence during the intermediate stage were more likely to engage in hazardous drinking, though no significant effect was found on acculturative stress. This study provides valuable insights for policymakers aiming to reduce negative psychological outcomes in vulnerable populations.